Tourism as a gift? An “ethnography of exchanges” and the offer of an alleged community-based tourism experience in Anã / Santarém / Pará - Assis, Giselle Castro (2019)
This article intends to demonstrate that the experience of tourism carried out in the community of Anã/Santarém/Pará includes several relations of reciprocity, according to Mauss’ conception (1925/2017).  For this author, the Gift is ambivalent, as it is simultaneously interested and disinterested, willingly offered and at the same time obligatory. The ambivalent character of the Gift was understood by means of the notion of interest, as established by Bourdieu (2011). The field work followed the assumptions of the ethnographic research, and the methodological path was built from the conception of Lanna (2000) about the “ethnography of the gift”.  The data were collected through direct observation and interviews, in two periods: August of 2016 and January of 2017. We want to point out as main results: the observation of five reciprocity relations among the internal and external agents to the community of Anã, which involves many kind of “payments”, as Mauss defines it (1925/2017); the interpretation of tourism as a Gift in social environment in which the activity promotes the reciprocity of things and of its spiritual and symbolic meanings in an ambivalent way; the observation that the community does not hold autonomy to manage tourism in its territory. We consider that the experience of Anã did not amass, yet, the required elements to be regarded as a community-based tourism.